DEIKSIS DALAM NOVEL THE NOTEBOOK KARYA NICHOLAS SPARKS (SUATU ANALISIS PRAGMATIK) - Wowiling, Midta (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research entitled â€œDeiksis dalam Novel The Notebook Karya Nicholas Sparksâ€. There are some very common words in our language that canâ€™t be interpreted at all if we donâ€™t know the context, especially the physical context of the speaker. These are words such as here and there, this or that, now and then, yesterday, today or tomorrow, as well as pronouns such as you, me, she, him, it, and them. Some sentences of English are virtually impossible to be understand and if we donâ€™t know who is speaking, about whom, where and when and itâ€™s included in deixis. The objective of research is to identify and analyze the types of deixis and the deixis which is the most used in the novel The Notebook by Nicholas Sparks. This research focuses on the novel The Notebook which consists of 213 pages. The research uses qualitative approach in order to find out the types of deixis in the novel The Notebook by Nicholas Sparks supported by Levinsonâ€™s Theory. The result of this research shows that there are four types of deixis that could be found in the novel The Notebook by Nicholas Sparks such as person deixis (first person deixis like: my, I, mine, and me, second person deixis like: you, and third person deixis like: she, he, her, his, him, them, and they), temporal deixis like: today, yesterday, later, then ,now etc , spatial deixis like: there, here, discourse deixis like: this story, these things, and social deixis is about the different social class between human like low class, middle class, and high class, but in this research of the novel The Notebook by Nicholas Sparks the writer did not find the social deixis. Â  Keywords: Deixis, Novel, The Notebook, Pragmatics Analysis.